Looking Awry at the 50 Years of the Republic of Cyprus - Danos, Antonis (My University, 2010)
The exhibition, motivated by the 50th anniversary of the establishment of the Republic of Cyprus, aims at a critical self-examination and look upon the place and its people. It includes contemporary works by Cypriot artists, which ‘look awry’ – that is, they look in critical, examining, subversive, thoughtful and humorous ways – upon ourselves, our recent past, our present and whichever possible future. This ‘awry’ look (taking a cue from a short dialogue in Shakespeare’s Richard II, and the dialogue’s analysis by Slavoj Zizek, in “Looking Awry” [1989]), aims at ‘seeing’ ourselves and our state in its proper dimensions, in contrast to the ‘head on’, seemingly direct view that has been [re]produced by the official, dominant rhetoric of the institutions and the mechanisms that have been defining us, ever since the establishment of the Cypriot state. The exhibition includes paintings, sculptures, video art, constructions, audio-visual installations and short films, by the following artists (alphabetically): Yianna Americanou, Antonis Antoniou, Klitsa Antoniou, Helene Black, Marianna Christofides, Yiannos Economou, Mustafa Erkan, Tatiana Ferahian, GRUP 102 [Ozge Ertanin, Oya Silbery, Evren Erkut], Yioula Hatzigeorgiou, Andreas Karayan, Diomedes Koufteros, Georgios Koukoumas, Atesh Kozal, Lia Lapithi, Stella Michaelidou, Marina Olympios, Vicky Pericleous, Vicki Psarias, Andreas Savva, Christiana Solomou, Katy Stephanidou, Nicos Synnos, Elina Theodotou, Evgenia Vasiloude, Washing-Up Ladies (Marianna Karafidou, Lia Lapithi), Omer Yetkinel and Talat Gokdemri.
Keywords: Contemporary Cypriot Art; Cypriot artists